![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
đề là : Tìm gtnn nha
\(H=x^2+xy+y^2-3x-3y+3\)
\(=\left(x^2-2x+1\right)+\left(y^2-2y+1\right)+xy-x-y+1\)
\(=\left(x-1\right)^2+\left(y-1\right)^2+\left(x-1\right)\left(y-1\right)\)
\(=\left[\left(x-1\right)^2+2\left(x-1\right).\frac{1}{2}.\left(y-1\right)+\frac{1}{4}\left(y-1\right)^2\right]+\frac{3}{4}\left(y-1\right)^2\)
\(=\left[\left(x-1\right)+\frac{1}{2}\left(y-1\right)\right]^2+\frac{3}{4}\left(y-1\right)^2\text{≥}0\) với mọi x, có GTNN là 0
Dấu "=" xảy ra \(\Leftrightarrow x=y=1\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
a) \(x^2-3x+xy-3y=\left(x^2-3x\right)+\left(xy-3y\right)\)
\(=x\left(x-3\right)+y\left(x-3\right)=\left(x+y\right)\left(x-3\right)\)
b) \(x^3-2x^2+x=x\left(x^2-2x+1\right)=x\left(x-1\right)^2\)
c)\(x^3+2x^2y+xy^2-9x=x\left(x^2+2xy+y^2-9\right)\)
\(=x\left[\left(x+y\right)^2-3^2\right]=x\left(x+y-3\right)\left(x+y+3\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
* \(3x+y=1\Rightarrow y=1-3x\)
\(M=3x^2+\left(1-3x\right)^2=3x^2+1-6x+9x^2=12x^2-6x+1=12\left(x^2-\dfrac{1}{2}x+\dfrac{1}{12}\right)=12\left(x^2-2.x.\dfrac{1}{4}+\dfrac{1}{16}\right)+\dfrac{1}{4}=12\left(x-\dfrac{1}{2}\right)^2+\dfrac{1}{4}\ge\dfrac{1}{4}\)\(\Rightarrow Min_M=\dfrac{1}{4}\Leftrightarrow x=y=\dfrac{1}{4}\)
\(N=x^2+xy+y^2-3x-3y\)
\(4N=4x^2+4xy+4y^2-12x-12y\)
\(4N=\left(4x^2+4xy+y^2\right)-12x-6y+9+3y^2-6y+3-12\)
\(4N=\left(2x+y\right)^2-2.3\left(2x+y\right)+9+3\left(y-1\right)^2-12\)
\(4N=\left(2x+y-3\right)^2+3\left(y-1\right)^2-10\ge-12\)
\(\Rightarrow N\ge-3\)
\(\Rightarrow Min_N=-3\Leftrightarrow x=y=1\)
\(\left(x^2-3x+xy-3y\right):\left(x+y\right)\)
\(=\left[\left(x^2+xy\right)-\left(3x+3y\right)\right]:\left(x+y\right)\)
\(=\left[x\left(x+y\right)-3\left(x+y\right)\right]:\left(x+y\right)\)
\(=\left(x+y\right)\left(x-3\right):\left(x+y\right)\)
\(=x-3\)